2018
DOI: 10.18203/2394-6040.ijcmph20180767
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the prevalence of anaemia amongst adolescent girls residing in selected slum of Bhopal city

Abstract: Background: Adolescence has been defined by the WHO as the period of life spanning the ages between 10 to 19 years. This is a vulnerable period in the human life cycle for the development of nutritional anaemia. The prevalence of anaemia among adolescents is 27% in developing countries and 6% in developed countries. The study was done with the objective to study the prevalence of anaemia among adolescent girls of selected urban slum of Bhopal.Methods: A cross sectional study was conducted for a period of 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 1 publication
2
23
1
1
Order By: Relevance
“…Similar results were obtained in studies conducted by Mandot and Bamnawat, Poyyamozhi et al ., Melwani et al ., Soman et al ., where the prevalence rates were found to be 41.1%, 62%, 67.77%, and 83.6% respectively. [ 9 18 19 20 ] Any developing nation, which has a prevalence of anemia more than 40%, is categorized as of severe public health significance. [ 21 ] This shows that the burden of anemia is very high among adolescent girls and it poses a major public health problem and interventions have to be carried out to improve their overall health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in studies conducted by Mandot and Bamnawat, Poyyamozhi et al ., Melwani et al ., Soman et al ., where the prevalence rates were found to be 41.1%, 62%, 67.77%, and 83.6% respectively. [ 9 18 19 20 ] Any developing nation, which has a prevalence of anemia more than 40%, is categorized as of severe public health significance. [ 21 ] This shows that the burden of anemia is very high among adolescent girls and it poses a major public health problem and interventions have to be carried out to improve their overall health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Chandrakumari, et al. 12 in Bhopal city showed that mean age of the study participants was 15.2±2.5 years. In the present study, prevalence was significantly more in girls belonging to lower socioeconomic class, 12 (46.2%) compared to other socioeconomic groups.…”
Section: Discussionmentioning
confidence: 93%
“…However, Melwani et al documented anemia 57.65% adolescent girls, of which 34.7% girls had mild anaemia, 44.9% girls have moderate and 20.4% girls had severe anaemia. 10 In our study, anemia was more prevalent (77.9%) in the younger age group of 10-13 years as compared to 72.8% observed in the older age group and it was statistically significant (p=0.048).Similar findings were reported by Kakkar et al in which level of anemia was significantly higher (p< 0.05) in early adolescent (10-13years) age group as compared to 58.3% in middle (14-16 years) and 48.7% in late adolescent (17-19 years). 5 Biradar et al however documented higher prevalence of anemia among the late adolescents i.e.…”
Section: Discussionmentioning
confidence: 99%